New or poorly known species of Sinodrepanus Simonis, 1985 (Coleoptera: Scarabaeidae: Oniticellini), with the first identification key for the genus - Montanaro, Giulio (Zootaxa, 2024)
The taxonomy and distribution of seven species of Sinodrepanus Simonis, 1985 (Coleoptera: Scarabaeidae: Oniticellini) is studied. Sinodrepanus schoenfeldi Montanaro, new species from India and Laos is described and illustrated. The morphologically similar and poorly known Sinodrepanus exsul (Sharp, 1875) is redescribed and illustrated, including the previously unknown female. The synonymy of S. arrowi (Balthasar, 1932) with S. rex (Boucomont, 1912) is confirmed and a lectotype of S. arrowi is designated. New distributional data on all three species, on S. falsus (Sharp, 1875), S. thailandicus Ochi, Kon & Masumoto, 2004 (new for Myanmar) and S. uenoi Ochi, Kon & Masumoto, 2004 (new for Laos) are reported. Comments on the distinction between S. besucheti Simonis, 1985 and S. tsaii Masumoto, Yang & Ochi, 2004 are made. Lastly, the first identification key to all Sinodrepanus species is provided.